Innovative trends - Şen, Zekai (Springer International Publishing AG, 2020)
Any time or space series may have structurally a linear or nonlinear deterministic component with a mathematical form throughout the whole record period.
Keywords: Innovative trends; Environmental Sciences; Ecology